AStudy on the Antibiotic Sensitivity Pattern in the Post - Operative Wards of a South Indian Hospital - J, Arun; S, Mohammed Saji; J, Francis; VI, Anand; S, Sundaran (Indian Journal of Pharmacy Practice)
Purpose: Surgical site infection (SSI) is a common post - operative complication which causes significant morbidity and mortality. Studies showed that surgical site infections prolong the hospital stay, healing of wound and add extra hospital cost. The study was undertaken to explore the antibiotic sensitivity pattern of the microorganisms isolated from the surgical wounds of the patients admit in the post-operative wards in a secondary care hospital. Methods: Microorganisms were isolated, identified and the antibiotic sensitivity pattern of the isolates were performed using standard methodology. Results: A total of 150 surgical wound swab samples were collected and scrutinized. Among this, 90 samples showed infections. Four microorganisms were identified in the 90 infection cases. Staphylococcus aureus and Pseudomonas species were the most common microorganisms isolated; other microorganisms were Escherichia coli and Streptococcus species. The empirical prescribing guidelines of the antibiotics were observed during this study. Conclusion: Ceftriaxone and ciprofloxacin showed maximum sensitivity pattern when compared to other antibiotics used in the hospital. Hospital disinfection and treatment protocols should be practiced vigorously and monitored regularly by hospital infection control committee to keep the incidences in control and hospital guidelines for antibiotic prophylaxis are warranted.
Keywords: Surgical site infection; Antibiotics; Microorganisms; Staphylococcus aureus